Experience of Flow and Creativity in Relation to the Teacher Effectiveness of Upper Primary School Teachers - Bosco, M. Arul John; Harichandan, Dhaneswar (JOURNAL OF INDIAN EDUCATION, 2021)
The teacher must be at the centre of the fundamental reforms in the education system’ (NEP 2020). A teacher plays a pivotal role not only in the capacity building of an individual but also in the development of a society. This study investigates the experience of flow and creativity in relation to the teacher effectiveness. The uniqueness of this research is that it uses hitherto unexplored concept of flow and its influence on teacher effectiveness in the Indian context. Flow describes a psychological state of optimal attention and engagement. The quantitative study, using the descriptive survey gathered data from 344 upper primary school teachers in Greater Mumbai Educational District. The correlational analysis has revealed a significant relationship between the experience of flow and teacher effectiveness. The regression equation estimates 35.9% as the influence of the experience of flow on teacher effectiveness. The study also found no significant relationship between creativity and teacher effectiveness.